An Exploratory Study of Perception and Practices of CSR in Small and Medium-Sized Enterprises Led by Women in Cameroon - FOUDA, Catherine Nicole BILOA (International Journal Of Management And Economics Invention, 2022)
Corporate Social Responsibility (CSR) symbolises companies’ response to the question of how to apply Sustainable Development (SD) values. For several decades, an abundant literature has focused on the responsible engagement of small and medium-sized enterprises (SMEs) in general but rarely in a gendered approach. The objective of this study is therefore to explore the perception of social responsibility issues of women-owned enterprises in Cameroon and to identify concretely their responsible practices. With this in mind, a theoretical framework has been constructed on the basis of Carroll Pyramid and a stakeholder (SH) perspective. After using Gioia Method in an interpretive style, the discourse analysis of in-depth interviews with five (5) SMEs run by women in the city of Douala revealed three main results. Firstly, CSR is perceived by women managers of SMEs more from an utilitarian, voluntary perspective than from a normative, binding one. Secondly, this vision of women SME managers seems to be justified by the theory of "care" which places community interest in the first place in a natural way to the detriment of individualism, self-interest. Thirdly, as the implementation of a CSR process requires large financial means, the actions carried out are primarily economic, more in favour of employees and customers.